Design Requirements Substantiation for an Automated Planting Unit for Potato Minitubers - A. S. Dorokhov; V. N. Zernov; S. N. Petukhov (Сельскохозяйственные машины и технологии)
The authors showed that the transition to the technology of virus-free minitubers mass production changed the machines requirements for planting original seed potatoes.(Research purpose) To develop a technological scheme and substantiate the design parameters of the planting apparatus of an automatic planter of potato minitubers.(Materials and methods) The development was based on an elevator-type planting apparatus. The authors decided to create a spoon design with the ability to grip and move into the guide casing one minituber in each spoon, eliminating the minitubers jumping from one spoon to another or pinching them when moving along the guiding casing to the furrow bottom. The diameters of the lower guide and upper drive rollers were theoretically substantiated in order to exclude the influence of the planting tubers sizes difference on the uniformity of their submitting into the furrow.(Results and discussion) The authors determined the minimum permissible elevator belt speed, which depended on the distance between the spoons on the elevator belt and the planting unit speed. The size of the upper driving reel diameter was justified from the condition that the spoon unfolded 180 degrees in at least 1.5 seconds, which ensured a tuber smooth transition to the back side of the spoon.(Conclusions) The authors developed a technological scheme of an automatic planting elevator type device for planting potato minitubers with a working speed of 6-9 kilometers per hour. It was found that the upper driving reel diameter was not less than 44 centimeters, and the lower guide roller diameter was not more than 12 centimeters. They showed that the double-sided design of scooping spoons with the possibility of installing replaceable bowls in them would ensure a high-quality planting of not only minitubers, but also subsequent reproductions of seed and ware potatoes with a tuber mass of 5-80 grams.